2009
DOI: 10.1093/geront/gnp037
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Medication Adherence Among Older Adults: Meta-Analysis of Adherence Outcomes Among Randomized Controlled Trials

Abstract: The findings document that interventions increase MA in older adults. The considerable heterogeneity in the magnitude of effects across studies and results of the moderator analyses demonstrate the need for additional empirical research to optimize interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
174
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 56 publications
6
174
4
4
Order By: Relevance
“…detect a change in weight compared to the day before. Therefore, patients need both tactical skills The strong emphasis on patient education activities in the interventions to improve adherence was also reported in a recently published meta-analysis, describing interventions to improve medication adherence in older adults [18]. They concluded that although teaching patients about their medications and disease is important, more emphasis should be placed on behavioral strategies to increase medication adherence.…”
Section: Discussionmentioning
confidence: 95%
“…detect a change in weight compared to the day before. Therefore, patients need both tactical skills The strong emphasis on patient education activities in the interventions to improve adherence was also reported in a recently published meta-analysis, describing interventions to improve medication adherence in older adults [18]. They concluded that although teaching patients about their medications and disease is important, more emphasis should be placed on behavioral strategies to increase medication adherence.…”
Section: Discussionmentioning
confidence: 95%
“…7,30,31 In some instances, males, non Caucasians, those who have less than a high school education, and are low-income have been found to be less adherent. [32][33][34] Depression. In general, studies relate depression with lower adherence.…”
Section: Patient Factorsmentioning
confidence: 99%
“…85,86 Problems with adherence are thought to be unintentional and are attributed to the patient's forgetfulness, difficulty with adapting to changes in the daily routine, or being asymptomatic. 34 However, patients may choose not to fill a script if they believe it will be ineffective or if the cost is prohibitive or they have no means of reaching a pharmacy. 87 Evidence demonstrates that adherence to treatment regimens that are documented to reduce mortality or the risk of other catastrophic outcomes (e.g., death) is poor.…”
Section: Adherence An Unrecognized Problemmentioning
confidence: 99%
“…This method was chosen because it offers cheap, easy method that had proven its capability to improve adherence with medication use (Conn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%